Breeding biology of tawes (Puntius gonionotus Bleelcer - Hoque, Muhammad Tafazzal; Ahmed, Abu Taweb Abu (Indian Journal of Fisheries, 2011)
Breeding biology of pond-reared to-oodsof Puntius gonionotus Bleeker was undertakenwith special reference to its inducedbreeding, using carp pituitary homogenate(cph), and other reproductive aspects. Anattempt was made to investigate anid developthe most viable technique under controlledhatchery condition lox seed production of thespecies.